An optimal policy mix for resource use - Marina Fischer-Kowalski; Dominik Wiedenhofer (WWWforEurope, 2014)
With reference to the use of material and energy resources, we seek to underline the need for a marked socio-ecological transition. Business-as-usual will fail in the face of an unprecendented rise in global demand, a rising price level and volatility of raw materials and indications of limited future supply. There needs to be a broad vision of such a transition, encompassing and extending beyond climate and resource policies and attractive for many different stakeholders and the general public. Key policy elements are carbon pricing, a shift of tax burdens from labour to resources, a shift in emphasis from improving labour productivity to resource productivity, and measures to improve the circularity of the economy. In the long run, Europe should be able to create a lifestyle in production and consumption that is globally sustainable. We build upon a new model, DYKE, that will represent Europe's energy and materials stocks and flows physically within the economic context and thus to internalize the functional interdependencies of energy and materials and simulate the impact of policies for the labour market and household income.
Keywords: H23; I31; O38; Q48; Q58; 330; Behavioural economics; Beyond GDP; Ecological innovation; European economic policy; Green jobs; Innovation policy; Socio-ecological transition